Biosynthesized Vitis vinifera seed gold nanoparticles induce apoptotic cell death in A431 skin cancer cells - Nirmala, J. Grace; Akila, S.; Nadar, M. S. A. Muthukumar; Narendhirakannan, R. T.; Chatterjee, Suvro (RSC advances, 2016)
Biologically synthesized gold nanoparticles provide many useful characteristics and can be used as carriers to deliver drugs because they are non-toxic and inert. In the present study, phytochemicals present in Vitis vinifera seeds were utilized as reducing agents for the synthesis of gold nanoparticles. The morphology, particle size and properties of V. vinifera gold nanoparticles (AuNPs) were characterized using transmission electron microscopy, X-ray diffraction, dynamic light scattering, Fourier transform infrared spectroscopy and zeta potential. The nanoparticles were then incubated for 24 h with human epidermoid skin cancer cells (A431) and were evaluated for their antiproliferative activities and induction of apoptosis. Spherical gold nanoparticles of ∼50 ± 5 nm were synthesized at room temperature within ten min and were capped with phytochemicals from V. vinifera seeds. At the inhibitory concentration (IC 50 ) of V. vinifera seed AuNPs (24.2 μM), they imparted cytotoxic effects, increased the level of reactive oxygen species, and induced apoptosis and apoptotic morphological changes in A431 cells significantly ( p < 0.01); these effects are associated with interference in mitochondrial membrane potential. This reduction in mitochondrial membrane potential probably initiated the apoptotic cascade in the nanoparticle-treated cells. Thus, gold nanoparticles synthesized utilizing Vitis vinifera seed phytochemicals may selectively target cancer cells, and the phytochemicals that are occluded within the nanoparticles may serve as anticancer agents, providing greater efficacy in killing cancer cells.